Influence of Children on Parental Purchase During Shopping in Supermarket - Sapkota, Ganga Prasad; Kafle, Sarad Chandra (Journal of Balkumari College, 2020)
Due to changing patterns of Nepalese life style and urbanization, parents are providing more value to their children and they are investing for children‘s tour, entertainment and for shopping that's why number of parental visit is found in park, shopping mall, zoo etc. Supermarket shopping has no longer history in Chitwan. Bhatbhateni supermarket is one of the famous and popular supermarket in this locality. This is famous among the purchaser because of facilities it has and varieties of goods available in the mall. Lift facility and ice-cream outside the mall attracting children towards this shopping mall. This study is focused on the purchasing behavior parents due to children’s demand who are visiting in Bhatbhateni supermarket(BBSM). Objectives of this study was to determine whether there is any influence of children on shopping behavior of their parents or not, if has influence what was the proportion of such parents, what are the major demands of children at BBSM. To fulfil the objectives of this study using purposive sampling of 60 customers attending in Bhatbhateni supermarket, Bharatpur is selected, the study is done on the basis of their response. Using structured questionnaire. The research design used is descriptive research design. Using SPSS data was compiled and analyzed. Simple frequency and percentage analysis has been carried to explain outputs, also chi-square test and Fisher's exact test has been carried to find out the association between variables under study. Outcomes of this study shows that children’s influence is their in parental purchase during shopping at BBSM. Parents, businessman and investors of BBSM are considering major beneficiaries of this study.